Effects of Low-Level Laser Therapy on M1-Related Cytokine Expression in Monocytes via Histone Modification. (19th February 2014) - Chen, Chia-Hsin; Wang, Chau-Zen; Wang, Yan-Hsiung; Liao, Wei-Ting; Chen, Yi-Jen; Kuo, Chang-Hung; Kuo, Hsuan-Fu; Hung, Chih-Hsing
Abstract : Low-level laser therapy (LLLT) has been used in the treatment of radiotherapy-induced oral mucositis and allergic rhinitis. However, the effects of LLLT on human monocyte polarization into M1 macrophages are unknown. To evaluate the effects of LLLT on M1-related cytokine and chemokine production and elucidate the mechanism, the human monocyte cell line THP-1 was treated with different doses of LLLT. The expression of M1-related cytokines and chemokines (CCL2, CXCL10, and TNF- α ) was determined by ELISA and real-time PCR. LLLT-associated histone modifications were examined by chromatin immunoprecipitation (ChIP) assays. Mitochondrial involvement in the LLLT-induced M1-related cytokine expression was evaluated by quantitative real-time PCR. Flow cytometry was used to detect the cell surface markers for monocyte polarization. The results showed that LLLT (660 nm) significantly enhanced M1-related cytokine and chemokine expression in mRNA and protein levels. Mitochondrial copy number and mRNA levels of complex I-V protein were increased by LLLT (1 J/cm 2 ). Activation of M1 polarization was concomitant with histone modification at TNF- α gene locus and IP-10 gene promoter area. This study indicates that LLLT (660 nm) enhanced M1-related cytokine and chemokine expression via mitochondrial biogenesis and histone modification, which may be a potent immune-enhancing agent for the treatment of allergic diseases.